A real-time ferroalloy model for the optimum ladle furnace treatment during the secondary steelmaking. (16th March 2019) - Kothari, Anil Kumar; Ranjan, Rajeev; Singh, Rama Shankar; Kumar, Gaurav; Kumar, Ashutosh; Agrawal, Ashish
ABSTRACT: Various means are applied in the steel making process to attain the desired chemistry. The final chemistry adjustments are made predominantly during the secondary metallurgy route in which ferroalloys (FAs) are added. With the availability of various FAs, it becomes necessary to identify the comparatively cheaper and optimum amount of FAs. The traditional practice of manually determining the quantity of FAs could not optimise the complete process. It is, therefore, necessary to determine the optimum FA addition without any human intervention. This paper presents a ferroalloy model in which a two-step incremental approach is adopted in ladle furnace (LF) to resemble the current operational practice. The model is designed such that no external intervention is needed to determine the required FA amount to be added. This results in low cost and high quality. The model after rigorous validation has been implemented in all three LFs in Tata Steel LD shop. This resulted in less FA consumption and achievement of the specified steel chemistry.